The Role of Sabang City Oral Literature as Cultural Education in Aceh - Yulsafli; Erfinawati Erfinawati (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aims to describe the role of oral literature in the culture of Sabang, Aceh, as it pertains to marriage customs and the delivery of dara baro and linto. The people of Sabang truly respect the intentions of customs and customs, and the tradition is still practiced by almost all of them today. Methods of qualitative research with descriptive analysis were employed. The study of data indicates the importance of oral literature as a life guide. This literature is also related to the development of education through the educational values contained in oral literature. The educational values contained in oral literature in Sabang are values that discuss issues of good and bad behavior, prohibitions, and what must be done to conform to the norms that have been taught, so that individuals can better direct and differentiate good and bad behavior. such as being trustworthy and not being malicious towards others. In Sabang's oral literature, cultural values pertain to minimizing natural calamities, the origin of an island, naming people depending on their location, and recompense. However, in social life, it is necessary to cultivate culture, as humans and culture cannot be separated. Humans who wish to adapt to their social surroundings must first familiarize themselves with the local culture.